(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
At present, the problem of helminthic invasions is very widespread in the clinical practice of primary healthcare physicians, particularly pediatricians and parasitologists. In Uzbekistan, helminthic invasions account for 90% of all parasitic diseases. Every year, more than 200,000 cases are registered in our country. In childhood, helminthic invasions often manifest as contributing factors to the development of chronic nutritional disorders, gastrointestinal dysfunction, intoxication, sensitization of the body, and weakened immunity.